Performance Analysis of Integral Process of Bio-Oil Production, Bio-Oil Upgrading, and Hydrogen Production from Sewage Sludge - Lida Simasatitkul; Apiwat Lakkhanasombut; Worawit Morin; Supachai Jedsadajerm; Suksun Amornraksa; Karittha Im-orb (E3S Web of Conferences, 2023)
This research investigated the production of bio-oil through the hydrothermal liquefaction (HTL) process using sewage sludge from wastewater, along with the hydrotreating of the bio-oil. The simulation process began with a wastewater flow rate of 460 tonnes/day, where the feedstock was divided into two streams. The first stream underwent the HTL process, while the other was directed towards hydrogen production. The resulting products included gaseous products, crude bio-oil, and heavy liquid. The crude bio-oil was further upgraded by introducing hydrogen, which was obtained through gasification and purified by gas separation using a palladium membrane. The primary product mainly comprised alkane, with a carbon content of 85.89% and hydrogen content of 14.11%. For the purification of gasoline, kerosene, diesel, and fuel oil, a fractionation distillation tower arrangement was designed. In addition, Additionally, the gaseous products underwent fractionation distillation to obtain 98% nitrogen and 99.9% liquid carbon dioxide. Considering the carbon footprint, it was observed that the bio-oil production process resulted in the highest greenhouse gas (GHG) emissions.
Keywords: Thermochemical Biomass Conversion Processes; Catalysis and Hydrodesulfurization Studies; Biofuel production and bioconversion